The two accretion states of the polar 1RXS J184542 in 2012 - Shchurova, A.V.; Pavlenko, E.P.; Malanushenko, V.P. (Advances in Astronomy and Space Physics, 2013)
We present the photometric investigation of the newly discovered magnetic cataclysmic variable (polar) 1RXS J184542 during four months in 2012. We used the CCD observations in R-band obtained with the 0.5-m ARCSAT telescope at the Apache Point Observatory. It was found that during this time the object changed its relatively high accretion state to the low one. There was a two-pole accretion at the high state and one-pole accretion at the low state.